The Girl Child : An Exposition Of Their Status - Senapati S.K; Bhattacharya S; Das D.K (Wolters Kluwer Medknow Publications, 1990)
The age of 0-15 years is crucial in terms of health, growth and development for a girl. Discriminations against the girl child start from birth and continue throughout the life of women. Socio- cultural factors compound the problem thus lowering the status of women in society. The present study was conducted in 8 villages of south 24 Parganas of West Bengal to recognize the status and problem of the girl child in a given socio- cultural reality. Using a multi- stage sampling procedure, 438 households with 1377 children (870 girls and 507 boys) of 0-15 years age- group were selected for collecting data on childrenâ€s health, nutrition, education, work pattern and motherâ€s opinion regarding issues related to the girl child.